Foreign Language Use in German and Turkish Magazine Advertisements: A Comparative Analysis - İrem Atasoy (Studien zur Deutschen Sprache und Literatur)
Advertisements today are influenced negatively by the use of foreign language as a persuasive tool. This is driven by globalization and the expansion of international brands and multinational advertising agencies. Advertisers frequently use foreign languages to attract attention and to evoke associations and internationality. Foreign words and phrases in advertisements are defined as linguistic codes that can be easily distinguished and remembered by individuals because of their distinctive phonological and morphological features. Such foreign words and phrases are emphasized by using various visual codes (e.g., font, point size, uppercase/ lowercase letters, and color) as typographic components. The use of foreign language in advertisements is one of the most analyzed subjects in the field of advertising language. This study seeks to examine the use of foreign languages in German and Turkish magazine advertisements. Adopting more linguistic and semiotic approaches, which treat language as a sign and advertisement as a message system, this paper focuses on the growing role of foreign languages in German and Turkish advertisements. The corpus consists of the first three online issues of Elle magazine published in 2021 in Germany and Turkey. The data are first classified quantitatively and qualitatively then analyzed in three steps applying linguistic and semiotic criteria. The first step involves the linguistic analysis of foreign words and phrases. The second step undertakes a semiotic analysis of the typographic elements employed as visual codes of foreign language usage in advertisements. The third step is devoted to a discussion and comparison of the results of the foregoing analysis.